2016
DOI: 10.3389/fnagi.2016.00278
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations of Prefrontal Brain Activity, Executive Functions, and Gait in Healthy Elderly Following Exergame and Balance Training: A Randomized-Controlled Study

Abstract: During aging, the prefrontal cortex (PFC) undergoes age-dependent neuronal changes influencing cognitive and motor functions. Motor-learning interventions are hypothesized to ameliorate motor and cognitive deficits in older adults. Especially, video game-based physical exercise might have the potential to train motor in combination with cognitive abilities in older adults. The aim of this study was to compare conventional balance training with video game-based physical exercise, a so-called exergame, on the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
143
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(156 citation statements)
references
References 98 publications
8
143
2
3
Order By: Relevance
“…Seven studies used the Nintendo Wii exergaming system with a variety of software packages (Ackerman et al, 2010;Hughes et al, 2014;Maillot et al, 2012;Pompeu et al, 2011;Şimşek and Çekok, 2016;Staiano et al, 2012;Zimmermann et al, 2014), four used interactive dance games with pressure-sensitive dance platforms used to response to visual cues for foot movements (Eggenberger et al, 2016;Eggenberger, 2015;Schattin et al, 2016;Schoene et al, 2013), three used interactive cycling/treadmill training wherein participants completed various tasks or avoided obstacles while pedaling/walking around virtual tracks (AndersonHanley et al, 2016;Barcelos et al, 2015;Mirelman et al, 2016) one used virtual-reality kayaking requiring coordinated upper-body movement to navigate virtual lakes/rivers (Park and Yim, 2016), one used the Microsoft Kinect system to deliver an aerobic exercise routine (Kimhy et al, 2015), and one used interactive co-ordination training involving throwing/catching games in a virtual environment (Chan et al, 2010). Control conditions were waitlist/usual treatment (N=5), aerobic exercise (N=5), balance, stretching and strengthening exercises (N=4) and health education sessions, reading, cognitive remediation or memory training (all N=1).…”
Section: Included Studies and Participant Detailsmentioning
confidence: 99%
“…Seven studies used the Nintendo Wii exergaming system with a variety of software packages (Ackerman et al, 2010;Hughes et al, 2014;Maillot et al, 2012;Pompeu et al, 2011;Şimşek and Çekok, 2016;Staiano et al, 2012;Zimmermann et al, 2014), four used interactive dance games with pressure-sensitive dance platforms used to response to visual cues for foot movements (Eggenberger et al, 2016;Eggenberger, 2015;Schattin et al, 2016;Schoene et al, 2013), three used interactive cycling/treadmill training wherein participants completed various tasks or avoided obstacles while pedaling/walking around virtual tracks (AndersonHanley et al, 2016;Barcelos et al, 2015;Mirelman et al, 2016) one used virtual-reality kayaking requiring coordinated upper-body movement to navigate virtual lakes/rivers (Park and Yim, 2016), one used the Microsoft Kinect system to deliver an aerobic exercise routine (Kimhy et al, 2015), and one used interactive co-ordination training involving throwing/catching games in a virtual environment (Chan et al, 2010). Control conditions were waitlist/usual treatment (N=5), aerobic exercise (N=5), balance, stretching and strengthening exercises (N=4) and health education sessions, reading, cognitive remediation or memory training (all N=1).…”
Section: Included Studies and Participant Detailsmentioning
confidence: 99%
“…The trial design is based on the results of the aforementioned animal studies and of the sole administration studies of either exergame training or omega-3 FA for older participants focusing on the brain. An exergame intervention was chosen because a combination of cognitive and motor training is expected to have positive effects on the elderly brain (Bamidis et al, 2014; Law et al, 2014; Schättin et al, 2016) and is able to ameliorate EFs in older adults (Eggenberger et al, 2016; Schättin et al, 2016). Motor training builds new synaptic connections while the cognitive part supports the preservation of the new build structure.…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…Furthermore, the investigators control adherence by a training adherence checklist. A previous trial testing the effects of similar games in older adults showed that this program will effect on EFs (Schättin et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…Neurofeedback has been used effectively in the past to modulate symptoms of attention deficit/hyperactivity disorder (Monastra, Monastra, & George, 2002) and other psychiatric orders such as anxiety, depression, and psychosis (Cheon et al, 2015;Schoenberg & David, 2014). Moreover, an exercise-based game and balance training regime has been shown to be effective in altering both biomechanics and brain activity (Schättin, Arner, Gennaro, & de Bruin, 2016). Conceptually similar paradigms can be used to implicitly improve sensorimotor control related to ACL injury risk, as prior work has demonstrated (Bonnette et al, 2019).…”
Section: Implications For Injury Preventionmentioning
confidence: 99%